A new species of Anoplodactylus (Arthropoda: Pycnogonida) from the Great Barrier Reef and discussion on the A. tenuicorpus-complex - Arango, Claudia P.; Krapp, Franz (Zootaxa, 2007)
A new species of sea spider is described from the Great Barrier Reef, Australia. Anoplodactylus perissoporus n.sp. is in a species complex of extremely slender and tenuous forms that have serrated heel spines and are known to inhabit Indo- West Pacific coral reefs. The new species is characterized by the multiple cement gland pores on femora of males. Otherwise the species is very similar to, and probably closely related to A. tenuicorpus. The species boundaries within the A. tenuicorpus complex are difficult to discern and are not clearly defined, especially for females. Other character sets seem necessary to indicate affinities and distribution patterns of the tenuicorpus complex.